Czy na pewno "inna" Rosja? O "Imperium" i "Buszu po polsku" Ryszarda Kapuścińskiego. - Pawluczuk, Wioletta (Acta Polono-Ruthenica, 2009)
The paper presents a voice in the discussion on blaming the writer for orientalization of the USSR, i.e., purposeful presenting the Union in a pathologic, unbalanced way in order to enhance the status of the West, including Poland. This accusation, however, loses its strength when one juxtapo- ses the image of the USSR (as presented in The Empire) with the image of Poland in the 50s and 60s in the twentieth century which appears in the volume of domestic reportages entitled The Polish Bush. Kapuciński's motherland is also presented as a country of fatalism, stagnation, superficiality of experience, lack of morality and sensitivity amongst the residents. If one finds it necessary to speak about orientalization, he/she should make a similar accusation against The Polish Bush or admit that the image described by the author shows only one aspect of the eastern empire. The aspect which is controlled by the ideology homo sovieticus. Closer analysis of Hebans authors text proves, however, that there is also the other, different Russia which has preserved in the USSR. It is the country when one can meet true Russians open-minded, friendly, and ready to bear responsibility for Other, Different people.